Letter from Max Bredig to Hermann Wismer, March 1940 - Bredig, Max Albert (1940)
Max Bredig (1902-1977) writes to a source in Switzerland, Hermann Wismer, who may be able to help deliver care packages to Bredig's sister and brother-in-law, Marianne Homburger (1903-1987) and Viktor Homburger (1888-1968), who are interned in the Gurs concentration camp in France.
Keywords: Bredig, Max Albert, 1902-1977; Homburger, Marianne, 1903-1987; Homburger, Viktor, 1888-1968; Gurs (Concentration camp); Jewish Holocaust (1939-1945)